PENDIDIKAN ISLAM TRANSFORMATIF DAN PEDAGOGI KRITIS PAULO FREIRE: STUDI KOMPARATIF DALAM MEMBENTUK KESADARAN KRITIS PESERTA DIDIK SEBAGAI AGEN PERUBAHAN SOSIAL - Wiasih; Cholid, Nur; Husna, Muhammad Ahsanul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the dominance of transmissive learning models in Islamic Religious Education, where teachers are positioned as the central source of knowledge and students as passive recipients. Such a model is considered insufficient for developing students’ critical awareness of social reality. This study aims to analyze the concept of critical consciousness in Paulo Freire’s Critical Pedagogy and Kuntowijoyo’s Transformative Islamic Education based on prophetic social science, compare both traditions systematically, and formulate an integrative synthesis model. This research employs a qualitative approach with library research as its method. The data were obtained from the primary works of Paulo Freire and Kuntowijoyo, as well as relevant scholarly journal articles. The data were analyzed using content analysis and comparative analysis based on eight dimensions: philosophical roots, concept of consciousness, educational goals, learning methodology, concept of praxis, role of learners, spiritual dimension, and orientation of social change. The findings show that Freire’s Critical Pedagogy and Transformative Islamic Education share several common points, including their rejection of transmissive education, emphasis on dialogue, integration of reflection and action, and positioning of learners as active subjects of social transformation. However, they differ fundamentally in terms of epistemology, spirituality, and the concept of freedom. This study proposes the Liberation-Transcendence Model, which integrates conscientization with tafakkur, praxis with the unity of knowledge and action, liberation with humanization and transcendence, and dialogue with halaqah. This model offers a conceptual framework for developing Islamic Religious Education that is critical, contextual, transformative, and transcendentally oriented.